Implementasi Pengontrolan Smart Home Menggunakan Voice Command Pada Facebook Messenger - Ahmad Khalid Azzam; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Usage of electricity is very wasteful. It can be easily controlled using system that's currently developed, a smart home. Smart home is a system to provide convenience for every inhabitant. In this study, Controlling of electronic devices at home from a distance is using a social media that is widely adopted by the public, Facebook messenger. Only by typing an instruction on the platform, users can control electronic devices anywhere. Lights and fan are examined electronic devices in this implementation. The function tested for lightings is turning off and turning on the tools. While the function tested for the fan is turning on slowly, changing the speed, and turning off the fan. To connect software applications that are easily operated with hardware such as lights and fans, this study uses Raspberry Pi. The commands received on the Facebook messenger chat will be sent to Heroku to process the language through wit.ai. It will be then sent to the database in firebase. The command is forwarded to the Raspberry Pi device which is connected to a relay that delivers electricity to the lights and fan devices. The system has been tested with various kind of testing. The results in translating the appropriate commands that can be processed are 100%, turn on and off the lights is 100%, and turn on, off and changing the speed of the fan is 100%.